New Journey Through Young Customer Experience in Omnichannel Context: The Role of Personalization - Rahmawati Rahmawati; Rois Arifin (Journal of Theoretical and Applied Management (Jurnal Manajemen Teori dan Terapan), 2022)
Objective: This study investigates the relationship between personalization and customer experience, with emotion and cognitive as the components through which the result repeats purchase intention. Design/Methods/Approach: This study uses purposeful sampling to enroll research participants based on the research objective. A total of 429 respondents met the criteria, and the hypotheses were tested using Smart PLS 3 software with Partial least squares (PLS) structural equation modeling. Findings: The results of this study confirm that customer experience is a significant attribute of consumer behavior in the omnichannel context. Specifically, the main findings of our research indicate that emotions and cognitive processes are influenced by personalization, a relationship that has been established in the online context. The findings also indicate that the emotional and cognitive components of the customer experience can influence purchase intention. Originality: Our framework is based on previous research and applies to a new construct with new phenomena. Practical/Policy implication: Our finding demonstrates that a better customer experience in an omnichannel context has a beneficial effect on repeat purchase intention, indicating that personalization might influence purchasing behavior. In essence, our finding enables companies to understand the linked nature of variables and consequently prioritize marketing initiatives in an omnichannel context.